Strengthening Character of Mahasantri Through Ta'limul Lail Activities at Ma'had Al – Jamiah UIN Raden Fatah Palembang - Annisa Naratu Mulya; Jhon Petet Pranata; Ayu Watawalaini; M Maryamah; Fitri Oviyanti (CV. Media Digital Publikasi Indonesia, 2024)
Character, known in Islam as morals, is an embedded trait in the human soul that spontaneously influences a person's attitudes, actions and behavior, whether towards good or bad. In the modern context, Muslims face global challenges, both internal in the form of backwardness in the education, political and economic sectors, and external in the form of negative accusations such as terrorism and anti-progress. Muslim youth, including mahasantri, have a strategic role as guardians of good religious values in society. However, strengthening the character of mahasantri is a necessity to face the challenges of shifting values in the era of globalization, especially in counteracting radicalism and intolerance. Character education, through a community-based approach, is an effective method to internalize good values in the mahasantri. One important effort in this context is through the Ta'limul Lail activity at Ma'had Al-Jami'ah, which is designed to deepen religious understanding, form positive habits, and improve noble morals. This activity not only has an impact on strengthening individual character, but also on the role of mahasantri as role models in society. Thus, Ta'limul Lail can be a strategic solution in shaping the character of mahasantri who are superior, religious, and contribute positively to the surrounding environment